Stress and charge transfer in uniaxially strained CVD graphene. Issue 12 (14th July 2016) - Bousa, Milan; Anagnostopoulos, George; del Corro, Elena; Drogowska, Karolina; Pekarek, Jan; Kavan, Ladislav; Kalbac, Martin; Parthenios, John; Papagelis, Konstantinos; Galiotis, Costas; Frank, Otakar
Abstract : Mechanical properties of graphene prepared by chemical vapour deposition (CVD) are not easily comparable to the properties of nearly perfect graphene prepared by mechanical cleavage. In this work, we attempt to investigate the mechanical performance of CVD graphene (simply supported or embedded in polymer matrix), transferred by two different techniques, under uniaxial loading with simultaneous in situ monitoring by Raman microspectroscopy. The level of charge transfer doping and strain is assessed using the vector analysis modified for uniaxial strain. The strain distribution across the samples varies significantly, owing to the growth and transfer process, which induces wrinkles and faults in the CVD graphene. In simply supported specimens, the stress transfer efficiency is generally very low and the changes in Raman spectra are dominated by variations in the charge transfer originating from the realignment of the domains on the substrate upon the application of strain. In contrast, samples covered with an additional polymer layer exhibit an improved stress transfer efficiency, and the alterations of charge doping levels are negligible. In fully embedded specimens, the variations in stress transfer efficiencies are caused by the size of the effective graphene domains defined by cracks, folds and/or wrinkles.